A newly developed cloning technique in sturgeons; an important step towards recovering endangered species - Fatira, Effrosyni; Havelka, Miloš; Labbé, Catherine; Depincé, Alexandra; Pšenička, Martin; Saito, Taiju (Scientific reports, 2019)
Several steps of sturgeon somatic cell nuclear transfer (SCNT) have been recently established, but improvements are needed to make it a feasible tool to preserve the natural populations of this group of endangered species. The donor cell position inside the recipient egg seems to be crucial for its reprogramming; therefore by injecting multiple donor somatic cells instead of a single cell with a single manipulation, we increased the potential for embryo development. Using the Russian sturgeon Acipenser gueldenstaedtii as a multiple cell donor and sterlet Acipenser ruthenus as the non-enucleated egg recipient, we obtained higher proportion of eggs developing into embryos than previously reported with single-SCNT. Molecular data showed the production of a specimen (0.8%) contained only the donor genome with no contribution from the recipient, while two specimens (1.6%) showed both recipient and donor genome. These findings are the first report of donor DNA integration into a sturgeon embryo after interspecific cloning. In all, we provide evidence that cloning with the multiple donor somatic cells can be feasible in the future. Despite the fact that the sturgeon cloning faces limitations, to date it is the most promising technique for their preservation.
Keywords: genom; Embryonic Development; klonování DNA; Animals; zachování přírodních zdrojů; Fishes; Endangered Species; zvířata; ohrožené druhy; ryby; Nuclear Transfer Techniques; techniky jaderného přenosu; Conservation of Natural Resources; Cloning, Molecular; Genome; embryonální vývoj